Improved immunobinding test using monoclonal antibodies for detection of Mycoplasma bovis in milk - Infante, F. (2002)
The aim of this study was to evaluate an improved immunobinding test (IBT) using monoclonal antibodies to identify Mycoplasma bovis in naturally infected milk. The IBT and the improved IBT were highly specific and had an immunologic sensitivity of 5 × 10(3) colony-forming units per milliliter. The results for the 2 methods agreed in the 130 milk samples tested. However, the IBT required 158 min, whereas the improved IBT required only 110 min. In addition, the improved IBT used smaller quantities of antibodies and conjugates.